2014
DOI: 10.1016/j.pediatrneurol.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine for Duchenne and Becker Muscular Dystrophies: Characteristics of Users and Caregivers

Abstract: BACKGROUND Complementary and alternative medicine is frequently used in the management of chronic pediatric diseases, but little is known about its use by those with Duchenne or Becker muscular dystrophy. METHODS Complementary and alternative medicine use by male patients with Duchenne or Becker muscular dystrophy and associations with characteristics of male patients and their caregivers were examined through interviews with 362 primary caregivers identified from the Muscular Dystrophy Surveillance, Trackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Only these data were available to generate residence history for each case; however, comparison of residence histories constructed from surveillance data with self-reports from a subgroup of caregivers showed a high concordance, suggesting we captured the years of residence for cases. Our previous comparison 48 of selected characteristics showed little difference between caregiver participants and nonparticipants, suggesting that our comparison of residence histories may be extended to all caregivers. Also, available medical records may have contained insufficient information for diagnostic milestones and disease progression, reflected in part, by differing percentages of possible cases across sites in the earlier quinquennia.…”
Section: Discussionmentioning
confidence: 82%
“…Only these data were available to generate residence history for each case; however, comparison of residence histories constructed from surveillance data with self-reports from a subgroup of caregivers showed a high concordance, suggesting we captured the years of residence for cases. Our previous comparison 48 of selected characteristics showed little difference between caregiver participants and nonparticipants, suggesting that our comparison of residence histories may be extended to all caregivers. Also, available medical records may have contained insufficient information for diagnostic milestones and disease progression, reflected in part, by differing percentages of possible cases across sites in the earlier quinquennia.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, Bar-Sela et al, showed that CAM improved significantly outcomes of cancer patients who completed six weekly sessions, regardless of their demographic characteristics ( Bar-Sela et al, 2013) . Researchers showed that Complementary and alternative medicine use was common in the Diabetes Mellitus ( Naja Mousa, Alameddine, Shoaib, Itani, & Mourad, 2014 ), Eczema ( Silverberg, Lee-Wong, & Silverberg, 2014) , Duchenne and Becker muscular dystrophies ( Zhu et al, 2014) patients. Studies have shown that welcomes people to complementary medicine techniques growing rapidly increasing in developed and developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Surveillance data were used for comparison of demographic characteristics between participants and all eligible individuals to examine possible participation bias. Chi‐square tests were conducted on case status, study site, child year of birth, child vital status, caregiver relationship, maternal age at interview, maternal race/ethnicity, and maternal education, and results have been reported by Zhu et al …”
Section: Methodsmentioning
confidence: 99%